The Role of Banana Corm Local Microorganisms and Irrigation Frequency in Improving Pakcoy Growth under Verticulture Condition - Pramesthi, Ardi Yoga; Sudharmawan, A. A.; Fauzi, Taufik (Jurnal Biologi Tropis, 2026)
Urban agriculture and verticulture systems have gained increasing attention as strategies to enhance food production in areas with limited land availability. Among leafy vegetables, pakcoy (Brassica rapa L.) is widely cultivated due to its short growth cycle and high market demand. This review examines the potential of banana corm-derived local microorganisms (MOL) and adaptive watering intervals as complementary approaches to improve pakcoy production in verticulture systems. A descriptive literature review was conducted by synthesizing studies related to banana corm MOL, liquid organic fertilizers, irrigation frequency, pakcoy growth, and verticulture-based cultivation. The reviewed literature indicates that banana corm MOL can enhance nutrient availability, stimulate microbial activity, and promote vegetative growth, leading to increased fresh biomass production. Watering frequency was also identified as a key factor influencing plant growth, nutrient uptake, and moisture availability within the restricted rooting environment typical of verticulture systems. The available evidence suggests that interactions between MOL application and watering management may affect pakcoy performance through their combin